Harvesting of Residual Soil Phosphorus on Intensive Shallot Farming in Brebes, Indonesia - Muliana Muliana; Arief Hartono; Syaiful Anwar; Anas Dinurohman Susila; Supiandi Sabiham (AGRIVITA, Journal of Agricultural Science, 2018)
Accumulated residual soil phosphorus (P) on shallots farming in Brebes can be harvested through the application of ameliorants or bio-fertilizers. The information on the effect of ameliorants and bio-fertilizers on soil P fractions is limited. The study objective was to evaluate the transformation of accumulated P to available forms by adding humic substance (CHS), bio-fertilizers (CBF), phosphate solubilizing bacteria (PSB), or phosphate solubilizing fungi (PSF) on soil from Brebes. The experiment was conducted in rhizobox that has two compartments, namely inner compartment (rooting area) and outside compartment (non-rooting area). Shallots were planted for 26 days, observed for their growth, and analyzed for their P absorption. Soil samples in rooting and non-rooting area were analyzed for their P fractions after planting. The results indicated that the addition of CHS, CBF, PSB or PSF increased the harvesting of residual soil P through its transformation to a more labile P as high as 0.67% in rooting area. The dynamic of transformation in rooting area gave better information of harvesting P. The capability of harvesting accumulated P was in the order of CBF, CHS, PSF and PSB. For harvesting residual P, addition of humic substance or bio-fertilizers should be made in the rooting area.